Impacts of Life Distributions on Reliability Analysis of Smart Substations - Ji-pu Gao; Xu He; Changbao Xu (Institute of Advanced Engineering and Science, 2014)
Most of the existing reliability analysis is based on exponential distribution which is convenient to calculation, whereas most intelligent electronic devices exhibit Weibull distribution. What kind of influence will life distribution have on the reliability and availability of a smart substation. This paper compares the reliability and availability of systems with different life distributions based on reliability block diagram and Monte-Carlo simulation, by treating the smart substations as non-repairable and repairable systems respectively. Simulation results proves the feasibility of substituting Weibull distribution with exponential distribution in engineering practice when the smart substations are treated as repairable systems, thus the life data estimation as well as the reliability analysis and calculation will be greatly simplified. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4833